PENGARUH PERPUTARAN KAS, PERPUTARAN PERSEDIAAN DAN PERPUTARAN PIUTANG TERHADAP RETURN ON ASSETS (ROA) PADA PT JAPFA COMFEED INDONESIA TBK PERIODE 2014-2023 - Novrianti, Rika; Kartono (Journal of Research and Publication Innovation, 2024)
The purpose of this research is to determine the effect of Cash Turnover, Inventory Turnover and Receivables Turnover on Return On Assets at PT. Japfa Comfeed Indonesia, Tbk for the period 2014 to 2023. The research method used by researchers in compiling a thesis is quantitative, namely conducting research that describes the company's financial condition expressed in the form of numbers. The data used is secondary data in the form of PT's financial reports. Japfa Comfeed Indonesia, Tbk over a period of 10 years from 2014 to 2023. The analytical methods used are classical assumption tests, linear regression tests, correlation coefficient analysis, coefficient of determination analysis and hypothesis testing. Based on the t test, partial cash turnover has no significant effect on Return On assets where thit -0.926 < t-tab 2.446 and a significance value of 0.390 > 0.05, partially inventory turnover has no significant effect on Return On assets where thit 0.907 < t-tab 2.446 and a significance value of 0.399 > 0.05 and partially receivables turnover has no significant effect on Return On assets where thit 0.638 < t-tab 2.446 and a significance value of 0.547 > 0.05 and based on the f test it states simultaneously cash turnover, inventory turnover and Receivables turnover has no significant effect on Return on assets where the Fhit value is 0.414 < F-tab 4.76 with a significant value of 0.749 > 0.05.